Gestodene, a novel positive allosteric modulator of PAR1, enhances PAR1-mediated human platelet aggregation - Park, So-Hyeon; Heo, Yunkyung; Kwon, Il; Jo, Sungwoo; Jeon, Hyejin; Lee, Yechan; Kim, Jieun; Heo, Ji Hoe; Namkung, Wan (Frontiers in Pharmacology, 2024)
Protease-activated receptor 1 (PAR1) is expressed in human platelets and can be activated by low concentrations of thrombin. Vorapaxar, a selective antagonist of PAR1, inhibits thrombin-induced calcium mobilization in human platelet, which is associated with an increased risk of bleeding. Conversely, the administration of a positive allosteric modulator (PAM) of PAR1 may pose a substantial risk of thrombosis due to inducing excessive platelet activation. In the present study, we performed a cell-based screening to identify PAMs of PAR1 and found a novel PAM of PAR1, gestodene, an oral contraceptive (OC). Gestodene enhanced both thrombin- and PAR1-activating peptide (AP)-induced intracellular calcium levels in a dose-dependent manner without altering PAR2 and PAR4 activity. Gestodene significantly increased PAR1-AP-induced internalization of PAR1 and phosphorylation of ERK1/2, and the enhancing effects were significantly blocked by vorapaxar. Furthermore, gestodene potently increased PAR1-AP-induced morphological changes in the human megakaryoblastic leukemia cell line MEG-01 cells. Remarkably, in human blood, gestodene exerted a robust augmentation of PAR1-AP-induced platelet aggregation, and vorapaxar effectively attenuated the gestodene-induced enhancement of platelet aggregation mediated by PAR1. Our results demonstrate that gestodene is a selective PAM of PAR1 and suggest one possible mechanism for the increased risk of venous thromboembolism associated with OCs containing gestodene.